Impact of Recreational Trampling on the Natural Vegetation in Termessos National Park, Antalya-Turkey - Selçuk Sayan; Osman Karagüzel; Meryem Atik (Journal of Agricultural Sciences)
Recreation activities could create various impacts on the natural environment. One of the recreation impacts is trampling that largely inevitable wherever nature visits occur. While consequences of trampling disturbance vary by the type of environment; vegetation is a significant indicator representing the form and degree of human-nature relation including recreation use. The aim of this study was to investigate the impact of recreational trampling on the Mediterranean natural vegetation in case of Termessos National Park, Antalya, so to contribute nature conservation planning and management. Based on a field sampling design species richness, vegetation height and vegetation cover were taken as impact indicators and assessed in trail and control plots. Study results showed that trampling impact on vegetation cover and height was already evident with the tendency of being higher on controls and lower on trails by use and use-related variations. But species richness was not on the verge of trampling disturbance yet, due to characteristics of the Mediterranean environment and likely competation for light on the trails. Accordingly species diversity in herbaceous vegetation level was also higher in trampled trail sites. Hereby the level of trampling impact is not at the threshold of alleviating species diversity and is rather in form of physical pressure on the vegetation, therefore most accessible and straightforward measure can be maintaining existing visitor numbers and to line up a visitor management programme such as dispersal of users from very heavily used trails to less used trails. Yet a site management plan that seeking a fine balance between recreation use and nature protection and taking the trampling impacts into account can help to maintain long-term conservation targets